Importance of the fund management company in the performance of socially responsible mutual funds - Belghitar, Yacine; Clark, Ephraim; Deshmukh, Nitin (Wiley, 2017)
We compare the performance of a sample of U.K.-based socially responsible investment (SRI) funds with similar conventional funds using a matched-pair analysis based on size, age, investment universe, and fund management company (FMC). We find that both the SRI and conventional funds outperform the market index about 50% of the time, even after fees. Subsample tests show that the SRI funds in our sample perform better in the pre- and postfinancial crisis periods but underperform during the financial crisis period. Importantly, we find that the FMC plays a major role in the outperformance of both SRI and conventional funds.